PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN CCTV PADA ZONA CCTV - Suwandi Suwandi (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
This research was conducted in the Zona CCTV Cirebon with the aim of knowing the quality of service on CCTV purchasing decisions in the Zona CCTV. The number of samples in this study were 95 respondents with random sampling. The researcher uses descriptive research method with quantitative approach using regression method. The results showed that service quality had an effect on purchasing decisions for CCTV in the Zona CCTV , in accordance with the results of hypothesis testing using t-test results obtained from tcount and ttable (13,2271,986) and P value (13,2271,986). 0.000 0.05), H0 is rejected and Ha is accepted, with a contribution of 65.3%, while the remaining 34.7% is the influence of variables outside of this study.